2016
DOI: 10.3109/00952990.2015.1125494
|View full text |Cite
|
Sign up to set email alerts
|

Smoking prevalence in urban and rural populations: findings from California between 2001 and 2012

Abstract: Background: Tobacco smoking and related health problems are still major public health concerns in the United States despite the declining smoking prevalence.Objectives: This study explored differences in smoking prevalence between urban and rural areas potentially relevant to tobacco control efforts in California. Pooled data from all CHIS cycles showed a similar pattern, with rates in Urban, Second-City, Suburban and Town/Rural areas being 15.2%, 15.2%, 13.1% and 17.3%, respectively. MethodsWeighted multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Nonetheless, opportunity to align lung screening availability with relevant clinical variables such as state-level lung cancer deaths or other population risk factors such as smoking prevalence remains as a public health consideration. Smoking trends continue to shift from cities, where most facilities are located, to rural areas(17)(18), increasing the challenge of optimizing screening facility distribution. Changes in smoking prevalence raise the need for further investigation on how should resources be allocated geographically(19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, opportunity to align lung screening availability with relevant clinical variables such as state-level lung cancer deaths or other population risk factors such as smoking prevalence remains as a public health consideration. Smoking trends continue to shift from cities, where most facilities are located, to rural areas(17)(18), increasing the challenge of optimizing screening facility distribution. Changes in smoking prevalence raise the need for further investigation on how should resources be allocated geographically(19).…”
Section: Discussionmentioning
confidence: 99%
“…The location and distribution of screening facilities by state were graphically represented using QGIS 2.18, open-source geographic information system (GIS) application that provides data viewing and analysis(17). We calculated the nearest neighbor index (NNI) within each state to investigate state-specific facility location clustering and dispersion patterns.…”
Section: Methodsmentioning
confidence: 99%
“…For example, several studies have shown that tobacco smoking [17,28,29] and alcohol consumption [30] are higher in rural and remote areas, whereas others have found no effect or a negative relationship with remoteness [31][32][33]. Living in regional and remote areas has been associated with unhealthier diet and decreased exercise in some studies [31,33,34]. This is consistent with Australian figures that show rates of daily smoking, overweight or obesity, lower levels of exercise and riskier alcohol consumption are higher in regional and remote areas than in major cities [35].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into geographic disparities in health behaviours have been limited by some key elements. For example, much of the literature on disparities in health behaviours is focused on younger adults (i.e., <50) [33,36,37]. Furthermore, many of the studies do not separate regional areas from rural or remote areas, collapsing all non-metropolitan residents into a "rural" group.…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco is a habit originating in cities [45,46] and so elder participants in the current sample who live in villages at high elevation tend to be non-smokers. Chromosomal changes that can cause NPB and NB become more frequent with age [4].…”
Section: Discussionmentioning
confidence: 94%